Review article of Sthoulya (Obesity) (International Journal of Food and Nutritional Sciences, 2019)
The present paper is based on Ayurvedic disease “Sthoulya.” Here we can compare it with modern disease “Obesity”. Man in the true sense is one who has the ability to discriminate and so, is a gifted creation. In the present era, Man has become alien to Nature and hence today, we have advanced medicines and many increasing diseases as well. We have complicated our living. In short, we are alien to or away from Nature. Since recent times, we have been talking about lifestyle disorders. Among these lifestyle disorders, a major share is attributed to Obesity, similar to its bulky nature. The following lines talks about obesity, lifestyle, prevention and management aspects. We talk about lifestyle without understanding life and knowing what lifestyle is. So, it is the knowing and understanding of life and all the aspects attributed to life synonymous with Ayurveda, which can address these issues effectively. There are many references for Ayurvedic management of Sthoulya that we have to apply in modern time. Finally main intention for presenting this paper is to share basic details of Sthoulya for proper Treatment.